Visualizing the Invisible: Social Constructions of Straight Identified Men Who Have Sex With Transsexuals and Feminized Gay Men On/Off Malaysian Film - Lim, David C. L. (Taylor & Francis, 2015)
Abstract This article examines an “invisible” group of Malaysian men who—although straight identified and gender socialized to eroticize and have sexual relations with natural-born females—also secretly have sex with transsexuals and/or feminized gay men, incidentally or occasionally. Specifically, the article looks at how these otherwise heteronormative men are socially constructed in 2 forms of social texts, namely, Malaysian films and interview-derived narratives of transsexuals and feminized gay men. These social texts are parsed through Simon and Gagnon’s (1986) theory of sexual scripting to yield 4 constructions of the men under focus: the accidental, the repentant, the volitional, and the cloacal. The contention of this article is that the invisibility of these men is causally linked to the prevailing cultural scenarios in Malaysia that are heavily shaped by political Islamism and weighted in favor of the heteronormative male gender/sex. The article argues also that the invisibility of these men does not render them static and that their sexual practices and the meanings they attach to them have been evolving radically since the mid-1990s, even as the cultural scenarios in Malaysia are becoming increasingly intolerant of nonheteronormative genders and sexualities. (Abstract by author)